Efficacy and Safety of Pioglitazone Add‐On in Patients With Type 2 Diabetes Mellitus Inadequately Controlled With Metformin and Dapagliflozin: A Systematic Review and Meta‐Analysis of Randomised Controlled Trials - Ubaid Khan; Zuhair Majeed; Muhammad Haris Khan; Ahmed Bostamy Elsnhory; Ahmed Mazen Amin; Anum Nawaz; Ahmed Raza; Hafiz Muhammad Waqas Siddque; Mustafa Turkmani; Mohamed Abuelazm (Endocrinology, Diabetes & Metabolism)
ABSTRACT Background Type 2 diabetes mellitus (T2DM) accounts for over 90% of diabetes cases worldwide. Pioglitazone, a thiazolidinedione, enhances insulin sensitivity by activating PPAR‐γ. Evidence on its efficacy and safety as an add‐on to metformin and SGLT2 inhibitors in inadequately controlled T2DM is limited. This systematic review and meta‐analysis evaluates pioglitazone's role as a third‐line therapy for improving glycaemic control in addition to metformin and Dapagliflozin. Methodology We conducted comprehensive searches across PubMed, CENTRAL, WOS, Scopus and EMBASE until December 2024. Pooled data were reported using risk ratio (RR) for dichotomous outcomes and mean difference (MD) for continuous outcomes, along with a 95% confidence interval (CI). This systematic review and meta‐analysis is registered with PROSPERO ID: CRD42024612005. Results We included three RCTs with 885 patients. Pioglitazone add‐on therapy significantly reduced HbA1c levels (MD: −0.41; 95% CI: −0.54 to −0.27, p = < 0.00001, I2 = 0%), fasting blood glucose (MD: −11.91; 95% CI: −16.34 to −7.48, p = < 0.00001, I2 = 0%), Homeostatic Model Assessment for Insulin Resistance (HOMA‐IR) (MD: −0.65; 95% CI: −1.05 to −0.25, p = 0.001, I2 = 4.89%), increased the rate of achieving HbA1c < 7% (RR: 2.09; 95% CI: 1.66 to 2.64, p = < 0.00001, I2 = 0%), and HbA1c < 6.5% (RR: 2.19; 95% CI: 1.36 to 3.53, p = 0.001, I2 = 0%). However, there was no difference regarding Homeostasis model assessment of β‐cell function (HOMA‐β) between the two groups (MD: 2.73; 95% CI: −5.24 to 10.70, p = 0.5, I2 = 27.53%). Conclusion Pioglitazone add‐on therapy significantly improved glycaemic control by reducing HbA1c, fasting blood glucose and HOMA‐IR while increasing the likelihood of achieving HbA1c targets. However, no significant difference was observed in HOMA‐β between groups. These findings suggest the potential benefit of pioglitazone in enhancing glycaemic outcomes in diabetes management.